REPRESENTATION OF ARISTOTLE’S RHETORICAL CONCEPTS IN GRETA THUNBERG’S SPEECH AS A GLOBAL CLIMATE ACTIVIST - El Fauziah, Ula; Bhuana, Gartika Pandu; Lisdawati, Ida (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2024)
Global advocacy is becoming increasingly crucial in the face of the escalating climate change catastrophe. Greta Thunberg's speech at the United Nations in 2019 captured the world's attention because of its message and presentation, which blended the power of Aristotelian rhetoric. Thunberg's speech included essential components of classical rhetoric, such as ethos (credibility), pathos (passion), and logos (logic), to make a compelling case for the urgency of climate change and the need for rapid action. This article examines how Thunberg's speech used these three aspects and how they might impact a worldwide audience and drive legislative change. This study demonstrates that the excellent use of rhetorical components made the address a watershed point in the history of the climate change movement, with a broad impact on global understanding of climate change.